OVERVIEW OF SKIN DIAGNOSTIC TECHNIQUES BASED ON MULTILAYER SKIN MODELS AND SPECTROPHOTOMETRICS - Michalska, Magdalena (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2021)
Today, spectrophotometrics is a promising tool for non-invasive examination of the optical properties of human skin. The spectrum obtained during the study is carefully analysed by models developed by many scientists. Developed multilayer models are designed to reflect the most faithful processes occurring in the skin, its layers and essential elements. Many skin diseases are diagnosed: vitiligo, hemangios, skin birthmarks, melanoma. The article provides an overview of interesting solutions using spectrophotometrics in the process of diagnosing skin diseases.